Ransomware Analysis - Lanza, Claudia; Lahmadi, Abdelkader; François, Jérôme (Taylor & Francis, 2025)
This book presents the development of a classification scheme to organize and represent ransomware threat knowledge through the implementation of an innovative methodology centered around the semantic annotation of domain-specific source documentation. By combining principles from computer science, document management, and semantic data processing, the research establishes an innovative framework to organize ransomware data extracted from specialized source texts in a systematic classification system.